Calculation of the wave parameters for sea dyke design and upgrading - Hung, Nguyen Manh; Nghia, Nguyen Khac; Dien, Duong Cong (Vietnam Journal of Mechanics, 2008)
Sea dyke system is the effective mean for protecting the coastal low-lying areas from storm attack (the most dangerous storm induced phenomena are storm wave and surges). The coastal zone of Vietnam is blessed with wide variety of natural resources but at the same time, it is also a highly storm hazard-prone region. The storm number 7 (DAMREY) arrived in the East Sea from 26th to 28th of September 2005 and hit the south part of Red river delta coastal zone and caused sea dykes breaches at some stretches along the sea dyke system of the Nam Dinh province and big property damages of the local communes. In order to cope with the storm activity which is reinforced in the future by climate change, a Science Technology program on the sea dyke upgrading from Quang Ninh to Quang Nam provided by the Ministry of Agriculture and Rural Development has been implemented from April 2007. One of the program’s project is “Determining the wave heights for sea dyke designed along the coastal line from Quang Ninh to Quang Nam” with the object to propose a method for the calculation of the wave parameters with appropriate accuracy, simple for used and suitable for the natural condition of the different sectors of coastal line of Viet Nam from Quang Ninh to Quang Nam provinces and to upgrade and fulfill the wave calculation guideline for sea dyke design and upgrading. In the paper, the authors present the results of the project concerning the input data, wave models and the calculated wave parameters with different returning periods for 5 sectors along the coastal line from Quang Ninh to Quang Nam. The obtained results afford the promising of using in the sea dyke design and upgrading.